Dynamics of the mitochondrial network during mitosis - Kanfer, G; Kornmann, B (Portland Press, 2016)
During mitosis, cells undergo massive deformation and reorganization, impacting on all cellular structures. Mitochondria, in particular, are highly dynamic organelles, which constantly undergo events of fission, fusion and cytoskeleton-based transport. This plasticity ensures the proper distribution of the metabolism, and the proper inheritance of functional organelles. During cell cycle, mitochondria undergo dramatic changes in distribution. In this review, we focus on the dynamic events that target mitochondria during mitosis. We describe how the cell-cycle-dependent microtubule-associated protein centromeric protein F (Cenp-F) is recruited to mitochondria by the mitochondrial Rho GTPase (Miro) to promote mitochondrial transport and re-distribution following cell division.